Hypotheses and lessons from a native moth outbreak in a low‐diversity, tropical rainforest - Paul C. Banko; Robert W. Peck; Stephanie G. Yelenik; Eben H. Paxton; Frank Bonaccorso; Kristina Montoya‐Aiona; R. Flint Hughes; Steven Perakis (Ecosphere, 2022)
Abstract Outbreaks of defoliating insects in low‐diversity tropical forests occur infrequently but provide valuable insights about outbreak ecology in temperate environments and in general. We investigated an extensive outbreak of the endemic koa moth (Scotorythra paludicola), which defoliated endemic koa trees (Acacia koa) over a third of their range on Hawai‘i Island during 2013 and 2014. At Hakalau Forest National Wildlife Refuge, we observed the dynamics of the outbreak and its effects on host trees, nutrient cycling, and insectivorous consumers in reforestation stands of densely planted koa and in natural forest stands of mixed koa and ‘ōhi‘a (Metrosideros polymorpha). Contrary to predictions of the resource concentration hypothesis, caterpillar biomass and defoliation severity were greater in the natural forest sites, where koa density was relatively low. Caterpillars preferentially consumed the most palatable koa foliage type (phyllodes), and koa initially refoliated with the least palatable foliage type (true leaves). Lightly defoliated small trees refoliated more quickly than did heavily defoliated ones but the opposite was true for large trees, which also produced a greater proportion of phyllodes. Mortality was greatest for heavily defoliated small koa. Caterpillar frass caused larger increases in soil nitrogen (N) than phosphorus (P) availability, with the greatest N increases in fine‐textured soils. Foliar N increased in alien grasses under koa canopies compared to grasses away from koa and to native woody understory species. Bird activity was influenced by ‘ōhi‘a flower abundance and the severity of koa defoliation; birds switched to outbreaking caterpillar prey, and they gained weight during the outbreak. Bat foraging times decreased during the outbreak, apparently because they became satiated quickly each night. Parasitoid wasps increased with caterpillar abundance but had little influence on outbreak dynamics. Reducing alien grass cover and increasing tree diversity would likely reduce the impacts of insect outbreaks and similar perturbations to native forests.